Chemical equilibration in hadronic collisions - Kurkela, Aleksi; Mazeliauskas, Aleksas (Physical review letters, 2019)
We study chemical equilibration in out-of-equilibrium quark-gluon plasma using the first principles method of QCD effective kinetic theory, accurate at weak coupling. In longitudinally expanding systems - relevant for relativistic nuclear collisions - we find that for realistic couplings chemical equilibration takes place after hydrodynamization, but well before local thermalization. We estimate that hadronic collisions with final state multiplicities dNch/dη≳102 live long enough to reach approximate chemical equilibrium, which is consistent with the saturation of strangeness enhancement observed in proton-proton, proton-nucleus, and nucleus-nucleus collisions.
Gesehen am 24.05.2019